2016
DOI: 10.1177/0300985816658098
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Enterococcal Spondylitis Caused by Enterococcus cecorum in Broiler Chickens

Abstract: Enterococcal spondylitis (ES) is a disease of commercial broiler chickens, with a worldwide distribution. Symmetrical hind limb paralysis typical of ES results from infection of the free thoracic vertebra (FTV) by pathogenic strains of Enterococcus cecorum . To determine the pathogenesis of ES, birds with natural and experimental ES were studied over time. In natural disease, case birds (n = 150) from an affected farm and control birds (n = 100) from an unaffected farm were evaluated at weeks 1-6. In control b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(112 citation statements)
references
References 34 publications
5
105
0
2
Order By: Relevance
“…However, E. cecorum may cause enterococcal spondylitis, femoral head necrosis, arthritis. Infection with E. cecorum can constitute a serious health problem, usually for commercial broiler chickens and broiler breeder flocks (2,7,12). Recently, E. cecorum-associated disease was reported in Pekin ducks and in racing pigeons (9).…”
Section: Occurrence Of Enterococcus Spp In Poultry In Poland Based Omentioning
confidence: 99%
“…However, E. cecorum may cause enterococcal spondylitis, femoral head necrosis, arthritis. Infection with E. cecorum can constitute a serious health problem, usually for commercial broiler chickens and broiler breeder flocks (2,7,12). Recently, E. cecorum-associated disease was reported in Pekin ducks and in racing pigeons (9).…”
Section: Occurrence Of Enterococcus Spp In Poultry In Poland Based Omentioning
confidence: 99%
“…E. cecorum was also isolated from a broiler flock with pericarditis, hepatitis, femoral head necrosis and/ or VO and the authors concluded that bacteremia and generalized infection seem to be important steps in the pathogenesis of the infection caused by this bacterium in broilers (Jung & Rautenschlein, 2014). This was also suggested by Borst et al (2017), who observed that E. cecorum isolates recovered from the intestine, spleen, and free thoracic vertebra (FTV) of broilers in natural cases of VO had matching genotypes, confirming that intestinal colonization with pathogenic strains precedes bacteremia and infection of the FTV.…”
Section: Enterococcus Cecorummentioning
confidence: 81%
“…Some evidences suggest that the higher incidence of enterococci-associated diseases in poultry may be due to horizontal spread of dominant E. cecorum clones that exhibit high pathogenicity (Kense & Landman, 2011;Boerlin et al, 2012). However, the source of pathogenic E. cecorum remains unknown (Borst et al, 2017). Moreover, bacterial strains with genotypes similar to those isolated from VO cases were rarely recovered from the ceca of birds with VO and the presence of these isolates was not statistically associated with a higher risk of disease (Borst et al, 2012).…”
Section: Epidemiology Of the Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria that translocated when the intestines were compromised could have already been eliminated from the spleen. On the other hand, a field study of E. cecorum-derived spinal BCO found that bacterial presence in the spleen persisted, with increasing incidence, for several weeks [37]. In general, however, the timing of pathogenic events preceding BCO (translocation, bacteremia, colonization of bone tissue, etc.)…”
Section: Discussionmentioning
confidence: 99%